Supported lipid bilayer formation: beyond vesicle fusion - Jackman, Joshua A. (2022)
Supported lipid bilayers (SLBs) are cell-membrane-mimicking platforms that can be formed on solid surfaces and integrated with a wide range of surface-sensitive measurement techniques. SLBs are useful for unravelling details of fundamental membrane biology and biophysics as well as for various medical, biotechnology, and environmental science applications. Thus, there is high interest in developing simple and robust methods to fabricate SLBs. Currently, vesicle fusion is a popular method to form SLBs and involves the adsorption and spontaneous rupture of lipid vesicles on a solid surface. However, successful vesicle fusion depends on high-quality vesicle preparation, and it typically works with a narrow range of material supports and lipid compositions. In this Feature Article, we summarize current progress in developing two new SLB fabrication techniques termed the solvent-assisted lipid bilayer (SALB) and bicelle methods, which have compelling advantages such as simple sample preparation and compatibility with a wide range of material supports and lipid compositions. The molecular self-assembly principles underpinning the two strategies and important experimental parameters are critically discussed, and recent application examples are presented. Looking forward, we envision that these emerging SLB fabrication strategies can be widely adopted by specialists and nonspecialists alike, paving the way to enriching our understanding of lipid membrane properties and realizing new application possibilities.